2017
DOI: 10.1016/j.celrep.2017.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Avian-to-Human Receptor-Binding Adaptation by Influenza A Virus Hemagglutinin H4

Abstract: Low-pathogenicity avian influenza viruses (LPAIVs) have caused a global concern to public health since the first novel LPAIV H7N9 outbreak occurred. The receptor-binding properties of the viral hemagglutinin are one key factor for efficient transmission and infection in humans. Recent evidence shows that H4 subtype viruses have been widely circulating in domestic poultry and human asymptomatic infections might have occurred. Here, we evaluated the receptor-binding properties of two representative isolates, avi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 50 publications
2
62
0
Order By: Relevance
“…For example, Q226L and G228S were detected in HA protein of both H4N6 swine isolates but rarely in avian isolates, and these mutations increased human-like receptor binding ability and could have further enhanced virus transmission ability in pigs (Fig. 4) [33, 34]. In summary, this study suggested that tissue tropisms of H4N6 avian IAVs affect their spillovers from wild birds to pigs.…”
Section: Discussionmentioning
confidence: 82%
“…For example, Q226L and G228S were detected in HA protein of both H4N6 swine isolates but rarely in avian isolates, and these mutations increased human-like receptor binding ability and could have further enhanced virus transmission ability in pigs (Fig. 4) [33, 34]. In summary, this study suggested that tissue tropisms of H4N6 avian IAVs affect their spillovers from wild birds to pigs.…”
Section: Discussionmentioning
confidence: 82%
“…In the evolving ways from avian to human tropism for H2-and H3-subtype IAVs, Q226L and G228S substitutions are key determinants, and the Q226L substitution appears to be more critical for human receptor recognition (Matrosovich et al, 2000;Rogers et al, 1983;Xu et al, 2010). Recent research revealed that Q226L substitution also plays a pivotal role in altering receptor-binding specificity for H4 HAs, and G228S substitution would decrease the affinity for avian receptors while enhancing binding to human receptors (Song et al, 2017). Although H5-subtype AIVs have not evolved a human receptor-binding preference in nature, several tropismswitching substitutions have been identified in laboratories The H7-SGTL mutant structures were superimposed with the structures of SH1-H7N9 HA in complex with avian (A and B) or human (C and D) receptor analogs for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…How other HA subtypes switch receptor specificity from α2,3-linked sialic acid to α2,6-linked sialic acid has also been studied. Different subtypes appear to require different sets of mutations to switch specificity toward α2,6-linked sialic acid-Q226L/ G228S for H4 HA (Song et al 2017), G225D for H6 HA (de Vries et al 2017b), V186G/K193T/ G228S, V186K/K193T/G228S or V186N/ N224K/G228S for H7 HA (de Vries et al 2017a), and K158aA/D193T/Q226L/G228S for H10 HA (Tzarum et al 2017) ("158a" indicates the insertion of an amino acid after position 158). Because of the structural variability of the RBS in different HA subtypes, it is not surprising that the mutational requirements for switching receptor specificity are different for different subtypes.…”
Section: Receptor Binding and Specificity Of Hemagglutininmentioning
confidence: 99%